ANALISIS KEPUASAN PENUMPANG TERHADAP PEMESANAN TIKET MELALUI TIKET ONLINE DAN PEMESANAN TIKET SECARA OFFLINE DI BANDARA XYZ - Thoha Putra Kurnianda; Hari Purwanto (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2021)
AbstractionThis research was conducted at XYZ Airport. Data search is done by interview technique and the questionnaire measures the level of Tiket.com service service satisfaction and the level of satisfaction of the ticket buyer Offline and direct observation, while the data obtained from the Tiket.com Part reports and offline ticket sellers, Data were analyzed using questionnaire analysis using SPSS . The results of the data show that service satisfaction for Tiket.com users and satisfaction of offline ticket servicesÂ Keywords: Information Systems, Information Systems Bus Ticket Booking, Website, PHP, MySQL.